Genetic research at a fivefold children's burial from medieval Berlin. (March 2015) - Rothe, Jessica; Melisch, Claudia; Powers, Natasha; Geppert, Maria; Zander, Judith; Purps, Josephine; Spors, Birgit; Nagy, Marion
Highlights: We performed genetic analysis of a fivefold medieval burial (15th century) from the St. Peters graveyard of Cölln/Berlin. We obtained for four individuals complete autosomal, Y-chromosomal and X-chromosomal STR profiles, autosomal and Y-chromosomal SNP data as well as complete coverage of the mitochondrial control region. Kinship analysis showed high evidence for full siblings for only two of the individuals. We discussed the genetic data within the archeological context to shed light on the background of the burial. Abstract: Berlin originated from the two twin cities Berlin and Cölln, which both were founded at the beginning of the 13th century. However the real date of their foundation as well as the origin of the first settlers is still unknown. On the Berlin site the historic city center is still visible in the Nikolaiviertel, but the medieval origin of Cölln disappeared almost completely. In 2007 a large scale excavation, which comprised an area of about 1700 m 2 of the historical center of the St. Peters church, recovers the remains of Cölln's first citizens and span a period of 500 years of medieval population. Here we present the first genetic analysis of a fivefold children's burial from excavations in Berlin. The genetic data unveiled next to ancestry and eye color data also the kinship and the gender of the five individuals. Together with the archeological context the new gained information help to shed more light on the possible reasons for this burial.